How the Body Works (Eyewitness Science Guides) - Parker, P. (london Dorling Kindersley, 1991)
Investigates the mysteries of the human body and lets readers discover, for themselves, facts such as how muscles work and how we see colour. 100 experiments - each using everyday household items - are included, with diagrams of the major body systems to show how each works.
Keywords: Science